2022
DOI: 10.1186/s12951-021-01220-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapeutic strategy of multimodal nanoconjugates for state-of-the-art brain tumor phototherapy

Abstract: Background The outcome of phototherapy, including photothermal therapy (PTT) and photodynamic therapy (PDT) for glioblastoma multiforme (GBM), is disappointing due to insufficient photoconversion efficiency and low targeting rate. The development of phototherapeutic agents that target GBM and generate high heat and potent ROS is important to overcome the weak anti-tumor effect. Results In this study, nanoconjugates composed of gold nanoparticles (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…In terms of PTT, the collective oscillation of electrons on the AuNP surface causes surface plasmon resonance (SPR) in light of specific wavelength to generate a strong extinction coefficient, thereby dissipate sufficient heat [ 33 ]. In our study, the proximate conjugation of PS on AuNPs accelerated its PDT outcome [ 34 ]. The phenomenon that enhances the ability of PS to generate ROS was denoted as metal-enhanced ROS generation (MERos) and it is mediated by intersystem crossover between PS and AuNP.…”
Section: Aunps For Combinational Ptt and Pdt In Gbm Treatmentmentioning
confidence: 99%
“…In terms of PTT, the collective oscillation of electrons on the AuNP surface causes surface plasmon resonance (SPR) in light of specific wavelength to generate a strong extinction coefficient, thereby dissipate sufficient heat [ 33 ]. In our study, the proximate conjugation of PS on AuNPs accelerated its PDT outcome [ 34 ]. The phenomenon that enhances the ability of PS to generate ROS was denoted as metal-enhanced ROS generation (MERos) and it is mediated by intersystem crossover between PS and AuNP.…”
Section: Aunps For Combinational Ptt and Pdt In Gbm Treatmentmentioning
confidence: 99%
“…Similarly, Kim et al. 177 described a nanoconjugate composed of Au nanosphere (Au nanoparticles) modified by photosensitizers by Au─S bonds for the treatment of glioblastoma multiforme with PTT and PDT. Zhang et al.…”
Section: Backbones and Structures Of Multifunctional Nanoparticlesmentioning
confidence: 99%
“…prepared a multifunctional nanoplatform (Ce6–AuNP–Lf) based on lactoferrin‐coated Au nanoparticles to deliver Chlorin e6 (Ce6) for the treatment of glioblastoma multiforme with phototherapy. 177 The PDT photosensitizer Ce6 was proximately conjugated on the surface of the PTT agent AuNP, leading to plasma crossover between Ce6 and AuNP that greatly improved the ROS production capacity of Ce6. Their results illustrated that Ce6–AuNP–Lf could effectively intervene in the progression of glioma and suppress the growth of tumors in a subcutaneous GBM mouse model by first applying PDT (671 nm), followed by PTT (532 nm).…”
Section: Application Strategies Of Multifunctional Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that the modi cation of drugs via lactoferrin (Lf) can target GBM by penetrating the blood-brain barrier (BBB) and increasing their stability and half-life of blood circulation [16,17] This was also possible because the lactoferrin receptor (LfR) is highly expressed in the blood-brain barrier (BBB) and GBM cells and on brain endothelial cells [18][19][20][21]. Moreover, Lf, a product of exocrine glands that found in many parts of the human body, prevents the partial rst-pass effects of hepatic metabolism and allow it to persist longer [22].…”
Section: Introductionmentioning
confidence: 99%